ANALISIS DATASET TINGGI GELOMBANG MAKSIMUM UNTUK PERIJINAN PEMANFAATAN RUANG LAUT BERESIKO RENDAH DI PERAIRAN PULAU SULAWESI - Muhammad Fadly; Andi Muhammad Ishak Yusma (Riset Sains dan Teknologi Kelautan, 2023)
With the rule of Indonesian Law No. 3 of 2023 concerning the Stipulation of Perpu 2 of 2022 concerning Job Creation and its derivatives/OMNIBUSLAW which have an impact on the management of licensing for the utilization of marine space, wave height datasets which are data that must be attached to the proposal for submission of a Marine Space Utilization Conformity Confirmation Approval (PKKPRL) are very important. However, most of the existing data requires further analysis and will make it difficult for small-scale marine space utilization businesses with activities that have a relatively low level of risk to the marine and coastal environment. Therefore, a dataset of wave height data that has been analyzed from the available data is needed so that it will be easily used by small-scale marine space utilization businesses in submitting PKKPRL proposals. This study presents an analysis of maximum wave height in the period 1999-2023 in Sulawesi seas obtained from monthly significant wave height data from altimetry satellites that have been reanalyzed by ECMWF (European Centre for Medium-Range Weather Forecasts) and presented in the form of digital maps. This dataset is expected to make it easier for small businesses to utilize it in the process of applying for marine space utilization permits.